Professional differentiation in network journalism - E V Prasolova (RUDN Journal of Studies in Literature and Journalism, 2013)
In the given article the requirements to be fulfilled within the journalist’s work in the conditions of the development of the information of the Internet-environment is considered. The conclusion is made that the authors of web-materials have to choose between the universalization and the narrow specialization of the profession. In the first case, journalists and bloggers need legal and editorial support.